Gas Hydrates: Applications and Advantages; Energies; Vol. 16, iss. 6 - Gaydukova O. S. Olga Sergeevna; Misyura S. Ya. Sergey Yakovlevich; Morozov V. S. Vladimir Sergeevich; Strizhak P. A. Pavel Alexandrovich (2023, 2023)
Title screen